STRATEGI PEMASARAN BENIH PEPAYA ARUM BERBASIS LAYANAN PURNA JUAL PADA PT TUNAS AGRO PERSADA DI WILAYAH PEMASARAN PROVINSI JAWA TENGAH - Putra Arafah Subhani; Ananti Yekti; Budi Wijayanto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aimed to identify internal and external factors and to formulate after-sales service-based marketing strategies for Pepaya Arum seeds at PT Tunas Agro Persada in Central Java. The research was conducted from November 2025 to February 2026 using a quantitative descriptive approach with purposive sampling involving 13 informants. Data were collected through structured interviews and observations and analyzed using SWOT and the Quantitative Strategic Planning Matrix (QSPM). The results showed total strength and weakness scores of 1.82 and 1.08, respectively, as well as opportunity and threat scores of 1.79 and 1.07. The Internal Factor Evaluation (IFE) score difference was 0.74, while the External Factor Evaluation (EFE) score difference was 0.72, indicating that the company is positioned in Quadrant I. The SWOT analysis generated 18 alternative strategies. Based on the QSPM analysis, the priority strategies were strengthening farmer group-based contract systems through integrated planting and harvesting schedules, supported by digital marketing (WO2), strengthening contract systems and price risk management (WT1), and utilizing marketing networks and partnership flexibility to expand market access (SO6).